PENGARUH PERSEPSI PENGUSAHA MIKRO KECIL DAN MENENGAH ATAS INFORMASI AKUNTANSI TERHADAP KEBERHASILAN PERUSAHAAN: Studi Empiris Pada Usaha Mikro Kecil dan Menengah Di Kecamatan Nangapanda Kabupaten Ende - Siga, Faustina G; Soleiman, Iriany D; Marselina, Apriana (Program Studi Akuntansi Universitas Flores, 2021)
The purpose of this study was to determine the effect of the perception of Micro, Small and Medium Enterprises on accounting information on the success of the company. Collecting data in this study using a survey questionnaire. Questionnaires were distributed to MSME owners who were involved in preparing the Financial Statements. The questionnaires that were divided were 30 and were re-filled completely and could be processed. The data collected was processed using the SSPS program. The statistical method used to test the hypothesis is descriptive analysis.The results showed that the entrepreneur's perception, accounting knowledge and experience in using accounting information had a positive effect on the success of the company. It is proven by the coefficient value of the entrepreneur's perception variable of 0.297 with tcount > ttable (2.459> 2.021) and a significant level of 0.018 <0.05. the regression coefficient value of the accounting knowledge variable is 0.300 with tcount > ttable (2.593>2.021) and a significant level of 0.013<0.05. the regression coefficient value of the entrepreneur